Student Activities 128 UMP Reserve Officers Training Unit (PALAPES) cadet officers commissioned as second - Mohd Azam, Muhamad Akhir (2019)
A total of 128 Universiti Malaysia Pahang (UMP) Reserve Officers Training Unit (PALAPES) from the army, navy and air force branches were commissioned as Cadet Officers in the Malaysia Armed Forces, with the rank of Second Lieutenants.